2015
DOI: 10.1016/j.dnarep.2015.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Functions that protect Escherichia coli from DNA–protein crosslinks

Abstract: Pathways for tolerating and repairing DNA-protein crosslinks (DPCs) are poorly defined. We used transposon mutagenesis and candidate gene approaches to identify DPC-hypersensitive Escherichia coli mutants. DPCs were induced by azacytidine (aza-C) treatment in cells overexpressing cytosine methyltransferase; hypersensitivity was verified to depend on methyltransferase expression. We isolated hypersensitive mutants that were uncovered in previous studies (recA, recBC, recG, and uvrD), hypersensitive mutants that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 80 publications
3
25
0
2
Order By: Relevance
“…RecA-independent and does not require DSB repair: The ability to repair double-strand DNA breaks through the RecA RecBCD-dependent homologous recombination pathway has been shown to promote survival to 5-azaC [30][31][32][33][34]. We confirmed the recA and recB were required to sustain viability during a 2 hour treatment with 5-azaC at various concentrations (Fig.…”
Section: -Azac-induced Mutagenesis Is Largelysupporting
confidence: 63%
See 1 more Smart Citation
“…RecA-independent and does not require DSB repair: The ability to repair double-strand DNA breaks through the RecA RecBCD-dependent homologous recombination pathway has been shown to promote survival to 5-azaC [30][31][32][33][34]. We confirmed the recA and recB were required to sustain viability during a 2 hour treatment with 5-azaC at various concentrations (Fig.…”
Section: -Azac-induced Mutagenesis Is Largelysupporting
confidence: 63%
“…DPCs can lead to the formation of double-strand breaks in mammalian cells [47]. In bacteria, tolerance of DPCs is diminished in recA and recBCD mutants [30][31][32][33][34], strains defective in DSB repair. RecA is not, however, required for the recovery of template-switch mutations induced by Figure 11.…”
Section: Discussionmentioning
confidence: 99%
“…Recombination and repair proteins play important roles in survival from damage due to DPCs and topoisomerase cleavage complexes. For example, RecA, which catalyzes strand exchange, and RecBCD, which prepares broken ends for HR, greatly improve survival from aza-C-induced DPCs [ 8 , 46 , 47 , 49 , 52 , 65 ] and quinolone-induced cleavage complexes [ 66 , 67 ]. We found that recA , recB and recC mutants were all markedly sensitive to TBCs generated by expression of M.EcoRII-C186A ( Fig 3 ; data summarized in Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…E . coli transposon mutants (kanamycin resistance gene) were created in a recent genetic screen [ 51 , 52 ] and are identified here as insertions (e.g. ssrA :: Kan ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation